Symbolic Solution to Complete Ordinary Differential Equations with Constant Coefficients - Juan F. Navarro; Antonio Pérez-Carrió (Journal of Applied Mathematics)
The aim of this paper is to introduce a symbolic technique for the computation of the solution to a complete ordinary differential equation with constant coefficients. The symbolic solution is computed via the variation of parameters method and, thus, constructed over the exponential matrix of the linear system associated with the homogeneous equation. This matrix is also symbolically determined. The accuracy of the symbolic solution is tested by comparing it with the exact solution of a test problem.